Investigation on the methods of measuring aggregate surface energy based on spreading pressure. (16th May 2023) - Luo, Rong; Wang, Xiang; Huang, Tingting; Tu, Chongzhi
Highlights: Gas adsorption method is applied to determine the surface energy of aggregate. The spreading pressure is the kernel in calculating the surface energy of aggregate. The determinations of specific surface area (SSA) and adsorption isotherm are two main steps in calculating spreading pressure. The O-K model is applied to describe the adsorption isotherm in terms of goodness of model fitting and physical significance. Abstract: Surface energy is applied to quantify the adhesion between aggregate and asphalt binder, which could be further utilized in evaluating the cracking resistance, or moisture sensitivity of asphalt mixtures. This paper investigated the determination of aggregate's surface energy based on the adsorption method. Two typical aggregates, limestone and diabase, were selected in this research. Determination of the spreading pressure of the test liquid on the selected aggregate is the kernel of the surface energy calculation. Two steps were required when calculating the spreading pressure, including the calculations of specific surface area (SSA) and the adsorption isotherm. The M-BET model, which was proven to be more feasible since the adsorption fitting was available in all pressure range, was utilized to calculate the SSA. Differing from other models, which need to set many adsorption assumptions, the Ono-Kondo (O-K) model was able to describe all types of adsorptions without the monolayer or multilayer adsorption assumptions. Therefore, the O-K model was further be applied to fit the adsorption data. In terms of the goodness of model fitting and physical significance, the O-K model was more appropriate than other adsorption models.